Quantitative digital imaging of banana growth suppression by plant parasitic nematodes - Roderick, H.; Mbiru, E.; Coyne, Danny L.; Tripathi, L.; Atkinson, H.J. (Public Library of Science, 2012)
A digital camera fitted with a hemispherical lens was used to generate canopy leaf area index (LAI) values for a banana (Musa spp.) field trial with the aim of establishing a method for monitoring stresses on tall crop plants. The trial in Uganda consisted of two cultivars susceptible to nematodes, a plantain, Gonja manjaya and an East African Highland banana, Mbwazirume, plus a nematode resistant dessert banana, Yangambi km5. A comparative approach included adding a mixed population of Radopholus similis, Helicotylenchus multicinctus and Meloidogyne spp. to the soil around half the plants of each cultivar prior to field planting. Measurements of LAI were made fortnightly from 106 days post-planting over two successive cropping cycles. The highest mean LAI during the first cycle for Gonja manjaya was suppressed to 74.863.5% by the addition of nematodes, while for Mbwazirume the values were reduced to 71.161.9%. During the second cycle these values were 69.262.2% and 72.262.7%, respectively. Reductions in LAI values were validated as due to the biotic stress by assessing nematode numbers in roots and the necrosis they caused at each of two harvests and the relationship is described. Yield losses, including a component due to toppled plants, were 35.3% and 55.3% for Gonja manjaya and 31.4% and 55.8% for Mbwazirume, at first and second harvests respectively. Yangambi km5 showed no decrease in LAI and yield in the presence of nematodes at both harvests. LAI estimated by hemispherical photography provided a rapid basis for detecting biotic growth checks by nematodes on bananas, and demonstrated the potential of the approach for studies of growth checks to other tall crop plants caused by biotic or abiotic stresses.